Application of green tourism in the Mount Rinjani National Park area to support sustainable tourism - Ilyas, Muh Nuh; Astawa, I Putu; Ginaya, Gede; Erawati, Ni Made Rai (International Journal of Green Tourism Research and Applications, 2022)
The purpose of this study is to analyze the application of green tourism in supporting the concept of sustainable tourism in the Mount Rinjani National Park (Taman Nasional Gunung Rinjani/TNGR) area, West Nusa Tenggara, Indonesia. The primary data of this study was generated through interviews with several informants, while the secondary data was obtained through a review of literature, books, journals, and online media. Techniques of data analysis using descriptive qualitative analysis. The results of the study reveal that the application of green tourism in the Mount Rinjani National Park area is quite good. This can be seen from the awareness of the community, organizations and related agencies in carrying out clean up and tree planting activities, both in tourist areas and the tropical rain forest with its rich biodiversity. Additionally, the green tourism concept is able to support sustainable tourism in national park tourism areas, especially in environmental, economic, socio-cultural sustainability, and environmental education.